Relationship Pattern of Fatherless Impacts to Internet Addiction, Suicidal Tendencies and Learning Difficulties for Students at SMAN ABC Jakarta: Relationship Pattern of Fatherless Impacts to Internet Addiction, Suicidal Tendencies and Learning Difficulties for Students at SMAN ABC Jakarta - Bunga Maharani Yasmin Wibiharto; Rianti Setiadi; Yekti Widyaningsih (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2021)
Fatherless is the absence of a father figure. Some impacts of fatherlessness are loneliness, openness, depression, self-control, and self-esteem. These factors can influence internet addiction and suicidal tendencies. It also can cause difficulty in the learning process for students. This study aims to determine the significant impacts caused by fatherlessness and the relation to internet addiction, suicidal tendencies, and learning difficulties. The method used is Partial Least Square. The results showed that the significant impacts caused by fatherlessness are loneliness, depression, and self-esteem. The impacts of fatherless that influence internet addiction are loneliness and depression. The impact of fatherlessness that influences suicidal tendencies is depression. Internet addiction and suicidal tendencies influence learning difficulties.